Aberdeen Burgh Records Database Search Portal - University of Aberdeen (2021)
"This is the search portal for the Aberdeen Burgh Records Project pilot database. It allows a search across text and images for 100 pages of Aberdeen Council Register volume 13 (Aberdeen City Archives: CA/1/1/13). [...] The date range for recorded business across the database is from 3 Oct 1530 to 3 Mar 1531, and the earliest and latest dates mentioned for particular entries are 15 Feb 1529 and 26 Sep 1531." [self-description]